The informal health sector and health care-seeking behaviour of mothers in urban Dhaka slums - Caldwell, Bruce K.; Rashid, Sabina Faiz; Murthy, Shivani (Journal of Population Research, 2016)
Includes bibliographical references (page 128-129).